Patients' lived experience of intensive care when being on mechanical ventilation during the weaning process: A hermeneutic phenomenological study. (August 2018) - Tingsvik, Catarina; Hammarskjöld, Fredrik; Mårtensson, Jan; Henricson, Maria
Abstract: Background: The medical and nursing care of the patient on mechanical ventilation has developed and proceeds in terms of ventilator functions, sedation strategies and patient participation. New data are needed to explore the weaning process from the patients' perspective. Therefore, the aim of this study was to explore the meaning of being a patient on mechanical ventilation during the weaning process in the intensive care unit. Methods: This study used van Manen's hermeneutic phenomenological approach. Interviews were conducted, including twenty former intensive care patients from three different hospitals in Sweden. Findings: Five themes emerged including thirteen related themes; Maintaining human dignity, Accepting the situation, Enduring the difficulties, Inadequate interaction and A sense of unreality. The experiences differed from each other and varied over time, and the same patient expressed both pleasant and unpleasant experiences. Weaning was not a separate experience but intertwined with that of being on mechanical ventilation in the intensive care unit. Conclusions: The patient's experiences differ and vary over time, with the same patient expressing various experiences. The favourable experiences were more clearly described, compared to previous research, this might depend on factors related to communication, participation and proximity to healthcare professionals and next-of-kin.